2016
DOI: 10.3390/dj4040040
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Influencing Adoption of Canadian Guidelines on Smoking Cessation in Dental Healthcare Settings in Quebec: A Qualitative Study of Dentists’ Perspectives

Abstract: Background: This study aimed to understand dentists’ perspective of the environmental determinants which positively or negatively influence the implementation of Canadian smoking cessation clinical practice guidelines (5As: Ask-Advise-Assess-Assist-Arrange) in private dental clinics in Quebec. Methods: This study used a qualitative design and an integrative conceptual framework composed of three theoretical perspectives. Data collection was conducted in individual semi-directed interviews with 20 private denti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Many studies have explored the factors that influence smoking cessation initiatives among patients with mental health diseases [8–10], patients with other chronic diseases such as hypertension [11, 12], TB patients [13], women [14, 15] and in the hospital settings [16, 17]. These studies have identified a variety of factors associated with the implementation of smoking cessation initiatives, including psychosocial factors (e.g., stress, self-efficacy, motivation and willpower), economic factors (e.g., cost), environmental factors (e.g., social support, peer support and pressure and supervision), risk perception and health awareness, provider awareness and attitude, to name but a few [8–17] .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have explored the factors that influence smoking cessation initiatives among patients with mental health diseases [8–10], patients with other chronic diseases such as hypertension [11, 12], TB patients [13], women [14, 15] and in the hospital settings [16, 17]. These studies have identified a variety of factors associated with the implementation of smoking cessation initiatives, including psychosocial factors (e.g., stress, self-efficacy, motivation and willpower), economic factors (e.g., cost), environmental factors (e.g., social support, peer support and pressure and supervision), risk perception and health awareness, provider awareness and attitude, to name but a few [8–17] .…”
Section: Introductionmentioning
confidence: 99%